Carboxymethyl cellulose or salt thereof

Granular carboxymethylcellulose or its salts with a specific bulk density are developed to prevent mamaco formation when mixed with water, enhancing solubility and productivity in lithium-ion battery production.

JP2025044841APending Publication Date: 2025-04-02DAICEL MIRAIZU LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023152638
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Carboxymethylcellulose (CMC) solutions often form aggregates or adhesive aggregations (mamaco) when mixed with water, leading to inhibited water permeation and prolonged dissolution times, which hampers productivity in various applications, including lithium-ion battery production.

Method used

The development of granular carboxymethylcellulose or its salts with a bulk density of 100 to 400 g/L, which suppresses the formation of mamaco when mixed with water, thereby enhancing immediate solubility and reducing dissolution time.

Benefits of technology

The granular form of CMC or its salts effectively prevents the formation of mamaco, allowing for efficient and rapid dissolution in water, thereby improving the productivity of lithium-ion battery production and reducing the likelihood of product defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044841000001
    Figure 2025044841000001
  • Figure 2025044841000002
    Figure 2025044841000002
  • Figure 2025044841000003
    Figure 2025044841000003
Patent Text Reader

Abstract

To provide a carboxymethyl cellulose or a salt thereof, capable of suppressing the formation of lumps when mixed with water.SOLUTION: Provided is a carboxymethyl cellulose or a salt thereof, in granular form, having a bulk density of 100 to 400 g / L.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to carboxymethylcellulose or a salt thereof. [Background technology]

[0002] Carboxymethylcellulose (hereinafter, also referred to as "CMC") is one of the representative water-soluble polymer materials, and is used in a wide range of applications, such as food, cosmetics, pharmaceuticals, and electrode materials for lithium-ion batteries. Although CMC is usually used in the form of an aqueous solution, it is prone to forming aggregates (aggregates or cohesive flocculations) when mixed with water. Once aggregates are formed, the penetration of water into the aggregates is inhibited, so it takes a long time to dissolve the CMC, and product productivity cannot be improved. Patent Document 1 discloses a method for granulation by spray drying in which a solvent-water-containing slurry of a carboxymethylcellulose ether alkali salt is atomized by flowing it down onto a rotating disk or by spraying it from a nozzle under at least one of an inert gas and air atmosphere. It also describes that the obtained CMC powder has a particle size of 70 to 200 μm or more in the whole, and the proportion of fine powder with a particle size of 20 μm or less is small, at 2.0% or less in the whole, and that the CMC powder has excellent solubility. Patent Document 2 describes that CMC or a salt thereof having a specific particle size distribution can be efficiently dissolved in water. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-73501 [Patent Document 2] Patent Publication No. 2021-21018 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide carboxymethylcellulose or a salt thereof that can suppress the formation of maltose when mixed with water. [Means for solving the problem]

[0005] The present disclosure encompasses the following aspects. [1] Granular carboxymethylcellulose or a salt thereof, having a bulk density of 100 to 400 g / L. [2] A material for lithium ion batteries, comprising the carboxymethyl cellulose or a salt thereof according to [1]. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide carboxymethylcellulose or a salt thereof that can suppress the formation of maltose when mixed with water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made within the scope of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. When multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. The lower and / or upper limit values ​​of the numerical range described in this disclosure are numerical values ​​within the numerical range and may be replaced with numerical values ​​shown in the examples. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments. Each configuration and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of configurations are possible as appropriate without departing from the spirit of this disclosure.

[0008] [Granular CMC or its salt] The carboxymethylcellulose (CMC) or salt thereof according to this embodiment (hereinafter also referred to as "granular CMC or salt thereof") is granular and has a bulk density of 100 to 400 g / L. "Granular" is used as a term to describe the shape. "Granular CMC or salt thereof" may be a "granule" or a "granulated product" of CMC or a salt thereof. "Granular CMC or salt thereof" may be a particle in which fine particles are adhered and aggregated in a granular form, and in that case, it can also be written as "a granular aggregate of fine particles of CMC or a salt thereof".

[0009] (CMC or its salt) CMC has a structure in which the hydroxyl group in the glucose unit constituting cellulose is replaced with a carboxymethyl ether group. CMC may be in the form of a salt. Examples of salts of CMC include alkali metal salts such as sodium salt, potassium salt, and lithium salt; alkaline earth metal salts such as calcium salt; and ammonium salt. These salts may be contained alone or in combination of two or more. Among these salts, sodium salt, ammonium salt, or lithium salt is usually used. CMC or its salt may be contained in combination. The method for producing CMC or its salt is not limited and can be synthesized by a known method.

[0010] The average degree of substitution (degree of etherification or DS) of CMC or its salt is preferably in the range of 0.1 to 3.0, and in the case of an aqueous composition for electrodes of a lithium ion battery, it is preferably 0.3 to 2.5, more preferably 0.4 to 2.0, even more preferably 0.5 to 1.6, even more preferably 0.6 to 1.4, particularly preferably 0.7 to 1.3, and most preferably 0.8 to 1.2. The higher the average degree of substitution, the better the solubility or immediate solubility, but if it is too high, it is difficult to generate hydrophobic interactions with the active material, which may reduce the coating strength, so it is preferable to keep it within the above numerical range.

[0011] The average degree of substitution (degree of etherification) can be measured by the method described below. (1) Accurately weigh out 1.000 g of sample and place in a porcelain crucible. After carbonization, completely incinerate at 630°C and cool at room temperature. (2) Accurately measure and add approximately 250 mL of ion-exchanged water and 40 mL of 0.05 mol / L sulfuric acid to a beaker. (3) Add (1) to (2), loosely cover, boil for 30 minutes, and then cool in cold water. After cooling, add 5 drops of phenolphthalein solution and neutralize with 0.1 mol / L sodium hydroxide aqueous solution. Perform a blank test in the same manner and calculate the degree of etherification using the following formula.

[0012] Degree of etherification = 162 x A1 / (10000-80 x A1) [In the formula, A1 is the amount (mL) of 0.05 mol / L sulfuric acid consumed by the bound alkali in 1 g of sample calculated as a dry matter, and is expressed by the following formula. A1=(B1-S1)×F1 / (W1×(1-M1 / 100))-alkalinity (In the formula, B1 is the amount of 0.1 mol / L sodium hydroxide aqueous solution consumed in the blank test (mL), S1 is the amount of 0.1 mol / L sodium hydroxide aqueous solution consumed in the actual test (mL), W1 is the sample weight (g), M1 is the drying loss of the sample (mass%), and F1 is the factor of the 0.1 mol / L sodium hydroxide aqueous solution). The loss on drying is measured in accordance with JIS P 8203:2010 (ISO638:2008), "Paper, paperboard and pulp - Determination of absolute dryness - Dryer method." The alkalinity can be measured by the following method. That is, about 250 mL of ion-exchanged water is placed in a beaker, and 1.000 g of precisely weighed sample is added little by little while stirring to dissolve, and then 5 mL of 0.05 mol / L sulfuric acid is added. The beaker is loosely covered and boiled for 10 minutes, and then cooled in cold water. After cooling, 5 drops of phenolphthalein solution are added, and neutralization titration is performed with 0.1 mol / L sodium hydroxide aqueous solution. A blank test is performed in the same manner, and the alkalinity is calculated by the following formula. Alkalinity = (B2-S2) x F2 / (W2 x (1-M2 / 100)) (In the formula, B2 is the amount (mL) of 0.1 mol / L sodium hydroxide aqueous solution consumed in the blank test, S2 is the amount (mL) of 0.1 mol / L sodium hydroxide aqueous solution consumed in the actual test, W2 is the sample weight (g), M2 is the drying loss of the sample (mass%), and F2 is the factor of the 0.1 mol / L sodium hydroxide aqueous solution.) The loss on drying can be measured in the same manner as in the average degree of substitution section.

[0013] (Bulk density) The granular CMC or its salt has a bulk density of 100 to 400 g / L. Due to the bulk density being 100 to 400 g / L, when the granular CMC or its salt is mixed with water, it is difficult for a granular CMC or its salt to generate a granular CMC or its salt. Since a granular CMC or its salt is difficult to generate a granular CMC or its salt, even if the molecular weight of the CMC or its salt is large, it can be efficiently dissolved in water in a short time. In other words, the granular CMC or its salt has excellent immediate solubility in water. This granular CMC or its salt can be dissolved in water under milder conditions than before. In other words, the granular CMC or its salt has excellent solubility in water. When this granular CMC or its salt is used in the production of an aqueous composition for electrodes of lithium ion batteries, the time required for the process of preparing the aqueous composition (or slurry composition) can be shortened, and the production of insoluble matter that causes product defects can be suppressed. As a result, the productivity (or yield) of lithium ion batteries can be effectively improved. Since the production of insoluble matter can be suppressed, additional effects can be obtained, such as the suppression of the occurrence of pinholes on the electrode surface and the ability to obtain an electrode layer with low electrical resistance. Here, "insoluble matter" refers to a substance that does not dissolve even when mixed for a long time, and is distinguished from undissolved matter, mamako.

[0014] The bulk density of the granular CMC or its salt is 100 to 400 g / L, preferably 150 to 380 g / L, more preferably 200 to 370 g / L, further preferably 250 to 360 g / L, and particularly preferably 280 to 350 g / L. In one embodiment, the bulk density of the granular CMC or its salt may be 305 g / L or 333 g / L, or may be within the range of the upper or lower limit of the above numerical range.

[0015] "Bulk density" is a tapped bulk density, which can be calculated by filling a graduated cylinder with precisely weighed granular CMC or its salt, tapping it several times from a height of about 5 cm, and reading the volume using the following formula. Details of the measurement method are as described in the examples below. formula: TIFF2025044841000001.tif14170

[0016] The bulk density can be adjusted, for example, by selecting a granulation method and adjusting the granulation conditions. For example, by adopting a fluidized bed granulation method or a tumbling granulation method as the granulation method, the bulk density tends to be lower. In the fluidized bed granulation method or the tumbling granulation method, the bulk density can be more easily adjusted to 100 to 400 g / L by adjusting, for example, the supply air temperature, supply air volume, atomized air volume, water content, etc. during granulation. For example, in the fluidized bed granulation method or the tumbling granulation method, the supply air temperature is set to 40 to 80°C (e.g., 55 to 65°C) and the supply air volume is set to 0.1 to 2.0 m 3 / min (e.g., 0.2-0.4m 3 By setting the flow rate to 30-50 L / min (e.g., 35-45 L / min) and the atomizing air volume to 30-50 L / min (e.g., 35-45 L / min), the bulk density can be more easily adjusted to 100-400 g / L. Also, by setting the water content to 1-30 mass% (e.g., 3-25 mass%) with respect to the raw material (100 mass%), the bulk density can be more easily adjusted to 100-400 g / L.

[0017] (total pore volume) In one embodiment, the total pore volume of the granular CMC or its salt measured by mercury intrusion porosimetry is preferably 1.3 to 3.5 mL / g, more preferably 1.5 to 3.0 mL / g, even more preferably 1.8 to 2.8 mL / g, more preferably 1.9 to 2.7 mL / g, and particularly preferably 2.0 to 2.6 mL / g. In one embodiment, the total pore volume of the granular CMC or its salt measured by mercury intrusion porosimetry may be 2.4 mL / g or 2.5 mL / g, or may be within the upper or lower limit of the above numerical range.

[0018] If the total pore volume is 1.3 to 3.5 mL / g, the formation of mamaco is more easily suppressed. The "total pore volume" is measured by mercury intrusion porosimetry. Details of the mercury intrusion porosimetry are in accordance with JIS R 1655:2003. The total pore volume can be measured by a mercury porosimeter. The principle of the mercury intrusion porosimetry is as described later in the section on porosity.

[0019] The total pore volume can be adjusted, for example, by selecting a granulation method and adjusting granulation conditions. As an example, by adopting fluidized bed granulation or tumbling granulation as the granulation method, the total pore volume tends to be high. In fluidized bed granulation or tumbling granulation, the total pore volume can be easily adjusted to within the above-mentioned predetermined range by adjusting, for example, the supply air temperature, supply air volume, atomized air volume, water content, etc. during granulation. For example, in fluidized bed granulation or tumbling granulation, the supply air temperature is set to 40 to 80°C (e.g., 55 to 65°C) and the supply air volume is set to 0.1 to 2.0 m 3 / min (e.g., 0.2-0.4m 3 By setting the flow rate to 30-50 L / min (e.g., 35-45 L / min) and the atomizing air volume to 30-50 L / min (e.g., 35-45 L / min), the total pore volume can be more easily adjusted to 1.3-3.5 mL / g. Also, by setting the water content to 1-30 mass% (e.g., 3-25 mass%) with respect to the raw material, the total pore volume can be more easily adjusted to 1.3-3.5 mL / g.

[0020] (Porosity) In one embodiment, the porosity of the granular CMC or its salt measured by mercury intrusion is preferably 65.0 to 90.0 volume%, more preferably 68.0 to 88.0 volume%, even more preferably 70.0 to 85.0 volume%, even more preferably 73.0 to 85.0 volume%, and particularly preferably 75.0 to 83.0 volume%. In one embodiment, the porosity of the granular CMC or its salt may be 79.3 volume%, or may be in a range with this as the upper or lower limit of the above numerical range.

[0021] When the porosity is 65.0 to 90.0% by volume, the formation of mamako is more easily suppressed. "Porosity" is measured by mercury intrusion porosimetry. Details of mercury intrusion porosimetry are based on JIS R 1655:2003. Porosity can be measured by a mercury porosimeter. Mercury intrusion porosimetry is a method for obtaining information on the physical shape of a solid by measuring the size and volume of pores in the solid. The principle of mercury intrusion porosimetry is to apply pressure to mercury to inject it into the pores of the object to be measured, and to measure the relationship between the pressure applied at that time and the volume of mercury that has been forced in (infiltrated). In this case, mercury infiltrates from the larger voids present in the particles of CMC or its salt.

[0022] The porosity can be adjusted, for example, by selecting a granulation method and adjusting the granulation conditions. As an example, by adopting a fluidized bed granulation method or a tumbling granulation method as the granulation method, the porosity tends to be higher. In the fluidized bed granulation method or the tumbling granulation method, the porosity can be easily adjusted to within the above-mentioned predetermined range, for example, by adjusting the supply air temperature, supply air volume, atomized air volume, water content, etc. during granulation. For example, in the fluidized bed granulation method or the tumbling granulation method, the supply air temperature is set to 40 to 80°C (e.g., 55 to 65°C) and the supply air volume is set to 0.1 to 2.0 m 3 / min (e.g., 0.2-0.4m 3By setting the flow rate to 100 rpm (e.g., 30 to 50 L / min) and the atomizing air volume to 30 to 50 L / min (e.g., 35 to 45 L / min), the porosity can be more easily adjusted to 65.0 to 90.0 volume %. Also, by setting the water content to 1 to 30 mass % (e.g., 3 to 25 mass %) with respect to the raw material, the porosity can be more easily adjusted to 65.0 to 90.0 volume %.

[0023] (Average particle size D50) The average particle diameter of granular CMC or its salt is preferably 50 to 300 μm, more preferably 80 to 280 μm, even more preferably 100 to 250 μm, even more preferably 110 to 230 μm, and particularly preferably 150 to 200 μm, as the volume-based cumulative 50% diameter D50. The average particle diameter (volume-based cumulative 50% diameter D50) can be measured by a conventional method according to the particle size, and may be measured with a laser diffraction particle size distribution meter, or may be calculated by analyzing an image based on an electron microscope. Furthermore, it can also be measured using an image-type particle size distribution measuring device (for example, "morphologiG3" manufactured by Malvern). In one embodiment, the average particle diameter of granular CMC or a salt thereof may be 171 μm or 176 μm as the volume-based cumulative 50% diameter D50, or may be within the range defined by these upper and lower limits of the above numerical range.

[0024] (Dispersion degree) The dispersion degree of the granular CMC or its salt measured using a powder tester is preferably less than 20.0, more preferably 10.0 or more and less than 20.0, even more preferably 10.0 or more and 19.0 or less, even more preferably 12.0 or more and 18.0 or less, and particularly preferably 13.0 or more and 17.0 or less. When the dispersion degree is within the above range, the formation of maltose is more easily suppressed. In addition, when the composition is made into an aqueous composition, the formation of insoluble matter is more easily suppressed.

[0025] The degree of dispersion is measured using a powder tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)). A 10 g sample is placed in the dispersion unit of the PT-X and dropped. The degree of dispersion can be calculated from the amount of powder that falls onto the watch glass using the following formula. Dispersion degree (%) = (10 (g) - amount of powder dropped onto the watch glass (g)) / 10 (g)

[0026] (Viscosity of aqueous solution) The viscosity of a 1 mass% aqueous solution of granular CMC or a salt thereof at a temperature of 25°C may be selected, for example, from the range of about 100 to 20,000 mPa·s, preferably 300 to 150,000 mPa·s, more preferably 400 to 10,000 mPa·s, even more preferably 500 to 8,000 mPa·s, and most preferably about 1,500 to 3,000 mPa·s.

[0027] In applications as lithium-ion battery materials (for example, as electrode materials for lithium-ion batteries), CMC or its salts themselves can act as resistors, and adding large amounts of CMC reduces battery performance. Therefore, there is a demand for high-viscosity products that can exert the desired functions (such as thickening effects) even when added in small amounts. On the other hand, from the viewpoint of improving productivity, there is a demand for CMC or its salt that has less undissolved matter (such as syrup) that causes product defects and can be dissolved quickly in a short time. However, the higher the viscosity in the aqueous solution, the more likely syrup is to occur and the longer the dissolution time, so these properties are in a trade-off relationship, and it has been difficult to satisfy all of them. The granular CMC or its salt of the present disclosure can be suitably used because it can effectively shorten the dissolution time even if the viscosity in the aqueous solution is high.

[0028] In the present disclosure, the viscosity of a 1% by mass aqueous solution of granular CMC or a salt thereof at a temperature of 25°C can be measured by the method described below. Put 100mL of ion-exchanged water into a dissolution bottle for viscosity measurement (hereinafter referred to as "viscosity bottle"), add a small amount of the sample (2.50 x X3) g that has been weighed out separately so that it does not become lumpy, and crush lightly with a glass rod. After sufficient swelling, add V3 (mL) of additional water to correct for ion-exchanged water calculated using the formula below, and dissolve completely while stirring occasionally with the glass rod. After dissolution, degas under reduced pressure, place the viscosity bottle in a thermostatic water bath until the liquid temperature reaches 25°C, stir the sample solution uniformly, and then measure the viscosity with a B-type viscometer at 60 rpm. Viscosity (mPa s) = scale reading x conversion factor V3=2.5×(100-X3-M3)-100 (In the formula, V3 is the amount of water added (mL) corrected for ion-exchanged water, X3 is the measured concentration (mass%), and M3 is the loss on drying of the sample (mass%). The loss on drying can be measured in the same manner as in the average degree of substitution section.

[0029] (Inhibition of the production of mamaco) The granular CMC or its salt of the present disclosure can suppress the formation of mamaco when mixed with water. The judgment of whether the formation of mamaco can be suppressed can be confirmed as follows: CMC is added to pure water at once so that the concentration of granular CMC or its salt is 1.5%, and the aqueous solution is stirred and mixed at a temperature of 25 ° C, a stirring speed of 4000 rpm, and a stirring time of 3 minutes, and filtered through a wire mesh with an opening of 106 μm. The presence or absence of mamaco can be judged by the presence or absence of transparent lumps on the wire mesh. With the granular CMC or salt thereof disclosed herein, no formation of mamaco is visually confirmed even with mixing times that are about one-tenth of the conventional time (the conventional normal mixing time is 30 minutes).

[0030] (Solubility in Water) The dissolution time when preparing a 1% by mass aqueous solution of granular CMC or a salt thereof may be, at a temperature of 25° C. and a stirring speed of 4000 rpm, for example, 10 minutes or less (e.g., 10 seconds to 8 minutes), preferably 6 minutes or less (e.g., 30 seconds to 5 minutes), more preferably 5 minutes or less (e.g., 1 to 4 minutes), and particularly preferably 4 minutes or less (e.g., 1.5 to 3.5 minutes). The dissolution time can be measured by the method described in the Examples below.

[0031] (Application) The granular CMC or its salt of the present disclosure is unlikely to produce condensation when mixed with water, so it can be preferably used in the production of aqueous compositions. For example, it can be preferably used as a lithium ion battery material (e.g., an electrode material for a lithium ion battery (e.g., a thickener, a dispersion stabilizer, etc.)).

[0032] [Method of producing granular CMC or its salt] Granular CMC or a salt thereof can be obtained by granulating the raw material CMC or a salt thereof. That is, the method for producing granular CMC or a salt thereof includes granulating the raw material CMC or a salt thereof.

[0033] (raw materials) As the raw material, the reaction solution of CMC or a salt thereof may be used as it is or after appropriate dilution, the particles of CMC or a salt thereof after synthesis may be used as it is, or the pulverized particles of CMC or a salt thereof may be used. When the reaction solution of CMC or a salt thereof is used as it is, it is preferable to granulate while drying in the granulation process. From the viewpoint of further improving the solubility in water by reducing the size of the insoluble matter when the obtained granular CMC or a salt thereof is mixed with water, the pulverized particles of CMC or a salt thereof can be used as the raw material. When the pulverized particles of CMC or a salt thereof are used, the method for producing granular CMC or a salt thereof may include pulverizing the particles of CMC or a salt thereof prior to granulation. The pulverization can be performed by a known method, for example, using a jet mill, a roller mill, a high-speed rotary pulverizer, a container-driven mill, etc.

[0034] (granulation process) Granulation can be carried out by a known granulation method. As the granulation method, a wet granulation method is preferred from the viewpoint of easily adjusting the bulk density, porosity, or total pore volume. Examples of the wet granulation method include a fluidized bed granulation method, a high-speed mixed stirring granulation method, an extrusion granulation method, a mixed stirring granulation method, and a rolling granulation method. From the viewpoint of more easily controlling the bulk density, porosity, or total pore volume of the obtained granular CMC or its salt, a fluidized bed granulation method or a rolling granulation method is preferred.

[0035] The fluidized bed granulation method is a method in which a fluidized bed of initially formed fine particles of CMC or its salt (raw material) is formed by an air flow, and while drying, water (or an aqueous solution of CMC or its salt) is sprayed into the layer, causing the fine particles to adhere to each other and aggregate, forming granules.

[0036] The type of fluidized bed granulation device is not particularly limited, and examples thereof include a normal type (FD) that can perform drying while granulating at the same time, and a pulsed fluidized bed type (PLS) in which the air at the bottom is pulsed. The installation position of the spray nozzle may be any of the top spray type, bottom spray type, and tangential spray type, but the top spray type is preferred from the viewpoint of easier suppression of the generation of mamako. In the top spray type, the installation position of the spray nozzle may be any of the upper, middle, and lower stages. As the fluidized bed granulation device, in addition to the fluidized bed granulation dryer and pulsed fluidized bed granulation dryer (PLS series) of Powrex Corporation, fluidized bed granulation dryers of companies such as Earth Technica Corporation, Nitto Machinery Finetech Co., Ltd., and Okawara Manufacturing Co., Ltd. can be used.

[0037] In the fluidized bed granulation method, the supply air temperature may be 40 to 80°C, 45 to 75°C, 50 to 65°C, 55 to 65°C, or 58 to 63°C. Air supply volume is 0.1 to 2.0 m 3 / min, 0.1~1.5m 3 / min, 0.2~1.0m 3 / min, 0.3~0.8m 3 / min, 0.3~0.5m 3 / min. The amount of atomized air may be 10 to 60 L / min, 10 to 50 L / min, 15 to 45 L / min, or 20 to 40 L / min. Also, it may be 20 L / min or 40 L / min, and these may be the upper or lower limit of the above numerical range.

[0038] When an aqueous solution of CMC or a salt thereof is used in the fluidized bed granulation method, its concentration can be appropriately adjusted within a range that allows spraying. The supply rate (spray rate) of water (or an aqueous solution of CMC or a salt thereof) may be 0.1 to 25 g / min, 0.5 to 20 g / min, 1 to 15 g / min, 1 to 10 g / min, or 3 to 7 g / min.

[0039] In the fluidized bed granulation method, the amount of water (or an aqueous solution of CMC or a salt thereof) sprayed is preferably 1 to 30 mass%, more preferably 3 to 28 mass%, and even more preferably 3 to 25 mass%, based on the total amount of the raw materials (100 mass%) in terms of hydration. In one embodiment, the amount of water (or an aqueous solution of CMC or a salt thereof) sprayed (hydration rate) may be 10 to 21 mass%, or may be 15 to 21 mass%, based on the total amount of the raw materials.

[0040] The rolling granulation method is a method of spraying water (or an aqueous solution of CMC or its salt) onto the rolling raw material, and coating it with fine particles of CMC or its salt to create spherical aggregates. The raw materials are as described above. The type of rolling granulation device is not particularly limited, and centrifugal fluidized granulation coating device (Freund Corporation), Roto Processor (Eromatic OE-Fuji Sangyo Co., Ltd.), Marmerizer (Fuji Paudal Co., Ltd.), VG Coater (Kikusui Seisakusho Co., Ltd.), etc. can be used.

[0041] In the tumbling granulation method, the concentration, supply rate, and spray amount (water content) of the aqueous solution of CMC or a salt thereof can be the same as those in the above-mentioned fluidized bed granulation method.

[0042] (drying process) The method for producing granular CMC or a salt thereof may include a drying step after the granulation step, if necessary. By including the drying step, the amount of water remaining in the granular CMC or a salt thereof can be easily adjusted. The drying method may be natural drying, or drying by heating and / or reducing pressure. Usually, drying is often performed by heating, and the heating temperature may be, for example, about 50 to 200°C (e.g., 60 to 150°C), preferably about 70 to 100°C (e.g., 80 to 90°C). The remaining amount of water may be, for example, about 30% by mass or less (e.g., 20% by mass or less) relative to the entire granular CMC or salt thereof after drying, and may be adjusted to preferably about 15% by mass or less (e.g., 10% by mass or less), and more preferably about 5% by mass or less (e.g., 1% by mass or less). In the fluidized bed granulation method, the granulation step may be followed by a drying step in the same bed.

[0043] (Crushing process) The method for producing granular CMC or a salt thereof may further include a pulverization step for pulverizing the obtained granular CMC or a salt thereof. The pulverization method is not limited, and can be performed by a known method using a jet mill, a roller mill, a high-speed rotary pulverizer, a container-driven mill, etc.

[0044] (Classification process) The method for producing granular CMC or a salt thereof may, if necessary, include classifying (or sieving) the obtained granular CMC or a salt thereof. By including a classification step, it is easy to adjust the desired roundness. In addition, it is easy to adjust the particle size distribution. The classification method includes conventional methods, such as classification utilizing the principles of fluid mechanics [dry classification (gravity classification, inertial classification, centrifugal classification, etc.), wet classification (sedimentation classification, mechanical classification, hydraulic classification, centrifugal classification, etc.)], sieving, etc. These classification methods can be used alone or in combination of two or more. Of these, classification is usually performed by sieving.

[0045] [Composition] In one embodiment, the granular CMC or its salt may be in the form of a composition. That is, the composition contains the above-mentioned granular CMC or its salt. The composition may be an aqueous composition (liquid, slurry, or paste composition) containing water and the above-mentioned granular CMC or its salt.

[0046] In the aqueous composition, the proportion of CMC or a salt thereof to the total amount of CMC or a salt thereof and water may be, for example, about 0.01 to 10 mass% (e.g., 0.1 to 5 mass%), preferably about 0.3 to 3 mass% (e.g., 0.5 to 2.0 mass%), and more preferably about 0.6 to 2 mass% (e.g., 0.7 to 1.5 mass%).

[0047] The water is usually pure water. The pH of the aqueous composition may be acidic, but is usually neutral or alkaline (particularly neutral).

[0048] The aqueous composition may contain other components other than CMC or its salt and water. For example, when CMC or its salt is used as an electrode material (such as a thickener and / or dispersion stabilizer) (i.e., when used as a material for a lithium ion battery), the aqueous composition may contain other electrode materials such as active materials (e.g., carbon materials such as natural graphite, artificial graphite, hard carbon, MCMB (mesophase microspheres), lithium titanate, etc.), binders (styrene butadiene copolymers, etc.).

[0049] The aqueous composition can be prepared by mixing granular CMC or a salt thereof, water, and other components that may be included as necessary. The order and method of mixing are not particularly limited, but from the viewpoint of effectively suppressing the formation of maltose, it is preferable to add granular CMC or a salt thereof (particularly slowly or in small amounts) while stirring the water using a stirrer or the like.

[0050] The stirring speed (rotation speed of the stirrer or stirring blade) when adding granular CMC or a salt thereof to water may be, for example, 10 to 6000 rpm, preferably 1000 to 6000 rpm, more preferably 1000 to 5000 rpm, even more preferably 1500 to 4800 rpm, and even more preferably 2000 to 4500. After the addition of CMC or a salt thereof is completed, stirring is usually continued until dissolution is completed (or the stirring torque becomes stable).

[0051] The stirring speed after the addition is completed may be equal to or higher than the stirring speed during the addition, but may be slow, for example, 10 to 1000 rpm (e.g., 50 to 800 rpm), preferably 100 to 500 rpm (e.g., 150 to 450 rpm), and more preferably 200 to 400 rpm (e.g., 250 to 350 rpm). In the present disclosure, even slow stirring can effectively shorten the dissolution time.

[0052] Examples of the shape of the stirring blades of the stirrer include turbine blades (e.g., edged turbine blades, flat or inclined turbine blades (fan turbine blades, disk turbine blades, etc.)), paddle blades (e.g., flat paddle blades, inclined paddle blades), propeller blades, Pfaudle blades, anchor blades (e.g., gate blades, etc.), ribbon blades (or helical ribbon blades) (e.g., multi-strand ribbon blades such as double ribbon blades, single ribbon blades, etc.). These stirring blades can be used alone or in combination of two or more kinds. Of these stirring blades, ribbon blades are preferred. When the stirring blade is a turbine blade, the stirring speed can be set to 1,000 to 100,000 rpm.

[0053] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of the present disclosure are disclosed below. <1> First aspect (granular CMC or salt thereof) [1-1] Granular carboxymethylcellulose or a salt thereof, having a bulk density of 100 to 400 g / L. [1-2] The carboxymethylcellulose or salt thereof according to [1-1], having a total pore volume measured by mercury intrusion porosimetry of 1.3 to 3.5 mL / g. [1-3] The carboxymethylcellulose or salt thereof according to [1-1] or [1-2], having a porosity of 65.0 to 90.0% by volume as measured by mercury intrusion porosimetry. <2> Second embodiment (granules of CMC or its salt) [2-1] Granules of carboxymethylcellulose or a salt thereof having a bulk density of 100 to 400 g / L. [2-2] Granules of carboxymethylcellulose or a salt thereof according to [2-1], having a total pore volume measured by mercury intrusion porosimetry of 1.3 to 3.5 mL / g. [2-3] Granules of carboxymethylcellulose or a salt thereof according to [2-1] or [2-2], having a porosity of 65.0 to 90.0% by volume as measured by mercury intrusion porosimetry. [2-4] A granule of carboxymethylcellulose or a salt thereof according to any one of [2-1] to [2-3], which is a lithium ion battery material. <3> Third aspect (composition) [3-1] <1> and / or a salt thereof, <2> A composition comprising granules of carboxymethylcellulose or a salt thereof according to claim 1. [3-2] The composition according to [3-1], which is a lithium ion battery material. <4> Fourth embodiment (aqueous composition) [4-1] Water, <1> or a salt thereof, <2> and a granule of the carboxymethylcellulose or a salt thereof according to claim 1. <5> Fifth Form (Lithium-ion Battery Materials) [5-1] <1> Carboxymethylcellulose or a salt thereof according to <2> Granules of carboxymethylcellulose or a salt thereof according to claim 1, and / or <4> A material for a lithium ion battery comprising the aqueous composition according to claim 1. EXAMPLES

[0054] The present disclosure will be described in more detail below by showing examples, but interpretation of the present disclosure is not limited to these examples.

[0055] [Raw materials] Raw material (1): Carboxymethylcellulose sodium salt, manufactured by Daicel Miraize Co., Ltd., "CMC Daicel Product No. 2200", degree of etherification (degree of substitution, DS): 0.93, average particle size D50: 101 μm, viscosity of 1% by mass aqueous solution (25°C, 60 rpm): 1657 mPa·s Raw material (2): Crushed raw material A, average particle size D50: 50 μm Raw material (3): Carboxymethylcellulose sodium salt, manufactured by Daicel Miraize Co., Ltd., "CMC Daicel Product No. 22005Y", degree of etherification (DS): 0.90, average particle size D50: 50 μm, 1 mass% aqueous solution viscosity (25°C, 60 rpm): 1990 mPa·s

[0056] [Example 1] (Preparation of Granular CMC-Na) 500 g of raw material (2) was placed in a pulsed fluidized bed (PLS) type granulator (Powrex, "Fluidized Bed Granulator Dryer (PLS)"), and then a fluidized bed of raw material (2) was formed by air flow. Pure water was sprayed into the layer while drying, causing the fine particles to adhere and aggregate, resulting in granulation, and a granular material of CMC-Na was obtained. The granulation conditions were as follows: <Granulation conditions> Supply air temperature: 60℃ Air supply air volume: 0.3m 3 / min Spray rate: 6-7g / min Atomized air volume: 40L / min Water content: 21% of the raw material Spray position: Top spray method (middle)

[0057] [Example 2] (Preparation of Granular CMC-Na) 500 g of raw material (1) was placed in a normal fluidized bed (FD) type granulator (Powrex, "Fluidized Bed Granulator Dryer (FD)"), and then a fluidized bed of raw material (2) was formed by air flow. Pure water was sprayed into the layer while drying, causing the fine particles to adhere and aggregate, resulting in granulation, and a granular material of CMC-Na was obtained. The granulation conditions were as follows: <Granulation conditions> Supply air temperature: 60℃ Air supply air volume: 0.3~0.5m 3 / min Spray rate: 3-7g / min Atomized air volume: 40L / min Water content: 10-14% of the raw material Spray position: Top spray method (middle)

[0058] [Comparative Example 1] (Preparation of Granular CMC-Na) 500 g of raw material (1) was placed in a granulator with stirring (VG) type (Powrex, "Stirring Mixing Granulator (VG)"), and then while stirring, a spray atomizer (Fulpura Co., Ltd., "No. 503") was used to squeeze the spray section to the maximum, and the lever was pulled once every 5 seconds to spray pure water, causing the fine particles to adhere to each other and aggregate, resulting in granulation and obtaining granular CMC-Na. The granulation conditions were as follows: <Granulation conditions> Water content: 20% of the raw material Spray rate: 5g / min Water addition method: 10% water was added and stirred for 5 minutes (intermittent spray) Blade rotation speed: 350 rpm Screw rotation speed: 3000 rpm Thereafter, the mixture was dried at 85° C. using a total exhaust dryer ("SPH-301S" manufactured by Espec Corporation) until the moisture content relative to the total amount of CMC-Na and water became 10% by mass or less.

[0059] [Comparative Examples 2 to 4] The raw materials (1) to (3) were used without being subjected to granulation or classification.

[0060] [Measurement and Evaluation] The following items were measured and evaluated, and the results are shown in Table 1.

[0061] (Bulk density) The tapped bulk density of the obtained sample was measured as follows. A 200 mL graduated cylinder was placed in a tip-prevention tube, and the cylinder was placed on a balance and tared. The sample was gently filled into the graduated cylinder up to 200 mL, and the weight of the sample was measured. A rubber stopper was attached to the graduated cylinder, and the volume was read after the graduated cylinder was dropped vertically from a height of 5 cm 10 times. The bulk density was calculated using the following formula. formula: TIFF2025044841000002.tif14170

[0062] (total pore volume) The total pore volume of the obtained sample was measured by mercury intrusion porosimetry. Details of the mercury intrusion porosimetry were in accordance with JIS R 1655:2003. The total pore volume was measured by a mercury porosimeter.

[0063] (Porosity) The porosity of the obtained sample was measured by mercury intrusion porosimetry. Details of the mercury intrusion porosimetry were in accordance with JIS R 1655:2003. The porosity was measured by a mercury porosimeter.

[0064] (Dispersion degree: Powder tester scattering degree) Using a powder property tester (Powder Tester PT-X (manufactured by Hosokawa Micron Corporation)), 10 g of a sample was placed in the dispersion unit of the PT-X and dropped. The degree of dispersion was calculated from the amount of powder that fell onto the watch glass using the following formula. Dispersion degree (%) = (10 (g) - amount of powder dropped onto the watch glass (g)) / 10 (g)

[0065] (Average particle size D50) The volume-based cumulative 50% diameter D50 was measured using an image particle size distribution measuring device ("morphologiG3" manufactured by Malvern).

[0066] (Whether or not Mamako is generated) The obtained sample was added to pure water at once so that the concentration of granular CMC or its salt became 1.5%, and the mixture was stirred and mixed at a temperature of 25°C, a stirring speed of 4000 rpm, and a stirring time of 3 minutes. The obtained aqueous solution was filtered through a wire mesh with an opening of 106 μm. It was visually confirmed whether or not there were transparent lumps on the wire mesh. With the granular CMC or salt thereof of Examples 1 and 2, no formation of mamako was visually confirmed even when stirred for 3 minutes, which is about one-tenth the mixing time of the conventional method. In Comparative Examples 1 and 2, a large number of granular CMC particles were visually observed, and the weight of the granular CMC particles on the wire mesh when soaked with water was approximately 1% of the amount of granular CMC or its salt added. Similarly, a large number of granular CMC particles were visually observed in Comparative Examples 3 and 4.

[0067] The water content in the obtained sample, the viscosity of the aqueous solution, and the dissolution rate in water can be measured as follows. (moisture content) The precisely weighed sample is dried in a thermostatic dryer at 105°C for 3 hours, and the moisture content is calculated from the weight after drying.

[0068] (Viscosity of aqueous solution) 100 mL of ion-exchanged water is placed in a dissolution bottle for viscosity measurement (hereinafter referred to as "viscosity bottle"), and a separately weighed sample (2.50 x X3) g is added little by little so as not to form lumps, and lightly crushed with a glass rod. After sufficient swelling, the corrected additional amount of ion-exchanged water V3 (mL) calculated by the following formula is added, and the solution is completely dissolved while stirring occasionally with a glass rod. After dissolution, the solution is degassed under reduced pressure, and the viscosity bottle is placed in a thermostatic water bath until the liquid temperature reaches 25°C. The sample solution is stirred uniformly, and then measured at 60 rpm with a B-type viscometer. The viscosity is calculated using the following formula. Viscosity (mPa s) = scale reading x conversion factor V3=2.5×(100-X3-M3)-100 In the formula, V3 is the amount of water added (mL) corrected for ion-exchanged water, X3 is the measured concentration (mass%), and M3 is the sample drying loss (mass%). Loss on drying is measured in accordance with JIS P 8203:2010 (ISO 638:2008), "Paper, paperboard and pulp -- Determination of absolute dryness -- Dryer method."

[0069] (dissolution time) 220 g of pure water is weighed into a cylindrical glass container with a diameter of 55 mm and a depth of 130 mm, and the temperature is adjusted to 25°C in a thermostatic bath. A torque meter ("Rotary Torque Meter TYPE YT" manufactured by Shinto Scientific Co., Ltd.) and a stirrer equipped with a helical ribbon-type stirring blade ("Three-One Motor BL1200" manufactured by Shinto Scientific Co., Ltd.) are attached to the cylindrical glass container. The helical ribbon-type stirring blade can have a ribbon width of 3 mm, a height of 80 mm, a width (width perpendicular to the rotation axis): 40 mm, a number of blades: single, and a number of spiral turns of the ribbon: 3 (a shape in which the ribbon turns three times in the height direction of 80 mm). While stirring the pure water at 750 rpm, 0.8 mass% of the sample (about 1.77 g) is slowly added over 5 to 10 seconds. After the addition, the stirring speed is immediately changed to 300 rpm and measurement of time is started, and the time it takes for the torque value to stabilize at a predetermined value is taken as the dissolution time. The maximum torque achievement rate is calculated as a percentage of the torque value that has stabilized at the above-mentioned predetermined value as a reference (100%).

[0070] [Table 1] [Industrial Applicability]

[0071] The granular CMC or salt thereof disclosed herein is less likely to produce maltose when mixed with water, and therefore can be preferably used in the production of aqueous compositions and has industrial applicability.

Claims

1. Granular carboxymethylcellulose or a salt thereof, Carboxymethylcellulose or a salt thereof having a bulk density of 100 to 400 g / L.

2. The carboxymethyl cellulose or salt thereof according to claim 1, having a total pore volume measured by mercury intrusion porosimetry of 1.3 to 3.5 mL / g.

3. The carboxymethyl cellulose or salt thereof according to claim 1 or 2, wherein the porosity measured by mercury intrusion porosimetry is 65.0 to 90.0% by volume.

4. A material for a lithium ion battery comprising particles of the carboxymethyl cellulose or a salt thereof according to claim 1 or 2.

Citation Information

Patent Citations

  • Process for granulating and drying alkali salt of carboxymethyl cellulose ether

    JP1996073501A

  • Carboxy methylcellulose or salt thereof and composition thereof

    JP2021021018A